Analysis of class I complexity induced spherical polytropic models for compact objects - Malik, Adnan; Mardan, S. A.; Naz, Tayyaba; Khan, Shiraz (Frontiers in Astronomy and Space Sciences, 2023)
In this research, we present a comprehensive framework that utilizes a complexity factor to analyze class I generalized relativistic polytropes. We establish class I generalized Lane-Emden equations using the Karmarkar condition under both isothermal and non-isothermal regimes. Our approach considers a spherically symmetric fluid distribution for two cases of generalized polytropic equation of state: (i) the mass density case μ_o and (ii) the energy density case μ. To obtain numerical solutions for both cases, we solve two sets of differential equations that incorporate the complexity factor. Finally, we conduct a graphical analysis of these solutions.